KEDUDUKAN ANAK LUAR KAWIN DALAM SISTEM HUKUM ADAT AMBON LEASE - Hetharie, Yosia (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2022)
In the community happens a in Ambon – Lease Islands many cases of children born out of wedlock .If there was outside woman who has borne a mate in costumary law forced marriage it will be done. A child prodigy mate against estate of inheritance the biological father in the system the sons of patrilineal and matrilineal basically just civil has links with his mother only while in a system of parentalstated his position child prodigy mate same of with a valid and entitled to on the estate of inheritance of your father biologist but inheritance that is based on the division of property in the axioms parimirma compassionate and some yurisprudensi the supreme court stating that child prodigy mate with a benefice valid and willingness with a base .There are also entitled to on the estate of inherited from their parents to the number of of an equal division , if child prodigy mate not with with a valid and child prodigy mate is achieving the right over all estate of inheritance their parents and of them.